Super group peer selection algorithm in hybrid layered P2P streaming system based on evolutionary game - Jing CHEN; Bing ZHOU; Chen-shan REN; Xiao-she DONG (Tongxin xuebao)
Due to high efficiency and good scalability,hybrid layered P2P architecture receives more and more impor-tance in P2P research and P2P streaming application fields recently.The blems about super peers selection are highly challenging because super peers must be selected from huge and dynamically changing network.A distributed super group peer(SGP) selection algorithm based on evolutionary game is proposed in this paper,in hich the SGP selection procedure is modeled based on evolutionary game framework firstly and its evolutionarily Moreover,a distributed Q-Learning algorithm (ESS-SGP) according to the mixed strategies by analysis is proposed for the peers to converge to the ESSs based on their own payoff history.Compared to the traditional random selected SGP P2P schemes,experiments results show that the proposed ESS-SGP algorithm achieves much better performance in terms of social welfare,average upload rate of SGPs,and keeps the upload capacity of the P2P streaming system increasing steadily with the number of peers increasing.